2021
DOI: 10.1111/petr.13979
|View full text |Cite
|
Sign up to set email alerts
|

Examining racial and socioeconomic disparity in the pediatric heart transplant evaluation

Abstract: The recent focus on racial inequalities highlights the need to evaluate and address systemic biases (often unrecognized and unintended) affecting minority groups in health care. Specific to pediatric heart transplantation, disparities in outcomes have been documented in national registry studies with lower survival after listing and transplantation in non-White patients. [1][2][3][4] However, registry databases do not extend to the time before waitlisting for transplantation. Therefore, the potential for bias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…Further, higher SES was associated with lower waitlist mortality for White and Hispanic patients, while higher SES was associated with greater waitlist mortality among Black patients 52 . A greater proportion of patients with identified “social concerns” at evaluation beyond SES and financial means were Black, with Black patients also having significantly lower income 47 . Five studies found no association between SES and pre‐transplant outcomes, including no associations with waitlist mortality, 27,28 likelihood of 28 or time to transplant, 49 or transplant knowledge 48 .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Further, higher SES was associated with lower waitlist mortality for White and Hispanic patients, while higher SES was associated with greater waitlist mortality among Black patients 52 . A greater proportion of patients with identified “social concerns” at evaluation beyond SES and financial means were Black, with Black patients also having significantly lower income 47 . Five studies found no association between SES and pre‐transplant outcomes, including no associations with waitlist mortality, 27,28 likelihood of 28 or time to transplant, 49 or transplant knowledge 48 .…”
Section: Resultsmentioning
confidence: 91%
“…However, one US/Canadian study found patients receiving dialysis prior to transplant were less likely to be Black 7 and another in Austria found no differences in rates of preemptive transplantation across ethnicity 19 . Two studies in the US found no differences in rates of referral or likelihood of transplant with regard to race 22,47 . Racial or ethnic identity was not associated with knowledge about living donation, understanding evaluation steps, or knowing insurance coverage 48 …”
Section: Resultsmentioning
confidence: 98%
“…Therefore, this analysis is just one part of our process of introspection as an institution to understand the inequities and lack of access within our own system and work to improve access and referral for these life‐saving therapies. One recent single‐center analysis similarly evaluated 133 patients referred for heart transplant evaluation in children 15 . The authors found that Black patients composed 44% of those referred with more markers of socioeconomic disadvantage; yet, race did not seem to impact listing for transplant 15 .…”
Section: Discussionmentioning
confidence: 99%
“…One recent single‐center analysis similarly evaluated 133 patients referred for heart transplant evaluation in children 15 . The authors found that Black patients composed 44% of those referred with more markers of socioeconomic disadvantage; yet, race did not seem to impact listing for transplant 15 . The authors similarly note the importance of continuing to evaluate upstream racial disparities during the referral and evaluation processes.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that health disparities, including race or ethnicity, insurance, income, and other sociodemographic barriers, 6‐10 contribute to delays in listing for organ transplantation in adult populations 10‐14 . Within pediatric transplant, similar disparities have been documented across racial, 5,13,15‐18 socioeconomic, 19 and other demographic factors (e.g., insurance type, gender) 20 . However, little research has compared waiting time between patients requiring various organ types, such as pediatric heart, liver, and kidney transplantation.…”
Section: Introductionmentioning
confidence: 98%